2017
DOI: 10.1213/ane.0000000000002056
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Volume Variation and Pulse Pressure Variation Are Not Useful for Predicting Fluid Responsiveness in Thoracic Surgery

Abstract: Dynamic preload indicators are not useful for predicting fluid responsiveness in VATS or open thoracic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 36 publications
2
42
0
Order By: Relevance
“…After simultaneous recordings of the baseline data including the SVI, SVV, PPV, and PSV, lactated Ringer’s solution was administered as an IV bolus of 10 mL/kg over 15 minutes to assess fluid responsiveness. Dogs were considered fluid responsive if SVI measured immediately after completion of the fluid challenge increased by 10% or more after volume loading [ 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…After simultaneous recordings of the baseline data including the SVI, SVV, PPV, and PSV, lactated Ringer’s solution was administered as an IV bolus of 10 mL/kg over 15 minutes to assess fluid responsiveness. Dogs were considered fluid responsive if SVI measured immediately after completion of the fluid challenge increased by 10% or more after volume loading [ 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Goal-directed fluid therapy (GDFT) based on the variations of pulse pressure and stroke volume 25 , or based on stroke volume or cardiac output itself 26 may be considered for thoracic surgery instead of fixed fluid infusion. However, the variations of pulse pressure and stroke volume are relatively inaccurate in thoracic surgery due to open chest, one lung ventilation, low tidal volume, etc 25 . Another shortcoming of GDFT is the possibility of fluid overload.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al found that a stroke volume variation threshold of greater than 15.5% had sensitivity and specificity, between 84.6% and 92.9%, suggesting that the Vigileo/FloTrac can be used to guide fluid therapy in the operating room. However, in thoracic surgery, the stroke volume variation is not a useful indicator of fluid responsiveness . The threshold value of the stroke volume variation for predicting fluid responsiveness may change when positive end‐expiratory pressure is applied.…”
Section: Discussionmentioning
confidence: 99%
“…However, in thoracic surgery, the stroke volume variation is not a useful indicator of fluid responsiveness. 19 The threshold value of the stroke volume variation for predicting fluid responsiveness may change when positive endexpiratory pressure is applied. We also observed a decrease in the SVC variation in response to the fluid challenge.…”
Section: Discussionmentioning
confidence: 99%